Advanced synthesis and comprehensive characterization of nanoparticle-reinforced epoxy-based biocomposites derived from modified palm oil - Sahal, Hakan; Aydogmus, Ercan; Canpolat, Erdal; Kaya, Mehmet (Elsevier, 2025)
In this research, new biocomposites were synthesized by two-step modification of palm oil (MPO). The raw material (MPOSA) was epoxidized in the first step and obtained by reacting with 4,4-diaminodiphenyl sulfone in the second step. Silicon carbide (SiC), MPOSA, bisphenol A diglycidyl ether, and epoxy resin were used to obtain the biocomposites. After this process, necessary physical tests and chemical analyses were performed. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) analyses were used to characterize the biocomposites. The research included measurements of bulk density, Shore D hardness, thermal conductivity, and thermal stability of the biocomposite. The results indicated that MPOSA reinforcement decreased the bulk density of the biocomposite in proportion to the doping level, and Shore D hardness tests revealed a decrease in hardness with the addition of MPOSA. The increase in MPOSA reinforcement also led to a reduction in the thermal conductivity coefficient. In experimental studies, the optimum reinforcement ratio was determined as 1 wt.% nano-SiC, 10 wt.% glass fiber, and 10 wt.% MPOSA. Excessive MPOSA reinforcement adversely affected the matrix structure and pore distribution of the nanocomposite due to aggregation due to increased intermolecular interaction. Thermal decomposition results showed that MPOSA reinforcement reduced the activation energy of the nanocomposite. This study successfully developed an economical, environmentally friendly, and easily processed biocomposite and contributed to the development of functional and sustainable alternatives.
Keywords: Silicon carbide; Modified palm oil; Epoxy biocomposite; Optimization; Characterization